INDIGENOUS INSTITUTIONS OF WOMEN: THE CASE OF WIJJOO AMONG ARSII OROMOO, ETHIOPIA - Lenin Kuto; Ayehu Bacha; Gemechu Taye (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This article aimed at investigating Wijjoo, an indigenous socio economic and political institution of Oromo women. Qualitative research methodology was employed in both data collection and analysis. Accordingly, data was collected through interview and focus group discussions from actual social context in 2014. This study has shown that Wijjoo is an exclusive assembly of Oromo women on which social, economic and political problems are discussed. Any injustice action against women is presented and further measures against such bigotry planned on its gathering. Butter which is considered as women property of women in Oromo culture also collected on Wijjoo meeting. The collected butter used by women’s for different purposes like household consumption, for marriage ceremony and other cultural rituals. Passing through different steps, Wijjoo gathering is concluded by smearing butter as a symbol of wetness, fertility and prosperity of human beings and cattle.Overall, the study concluded that Wijjoo plays a prominent role in ensuring the empowerment and autonomy of Oromo women as well as in nurturing their political, social and economic status. Therefore, recognizing and using this indigenous institution is vital in future policy formulation in the country for the fact that gender issues are central to the realization of sustainable development